Exergy efficiency of a hybrid system's main components for a standalone application - Kapan, Sinan; Bayrak, Zehra Ural; Celik, Nevin (Pergamon-Elsevier Science Ltd, 2025)
In this study, a standalone residential building in Izmir Turkiye is investigated by means of energy demands and consumption. Izmir is selected, since it has Mediterranean weather conditions, namely warm winters and hot summers. The house is considered to have a hybrid system, meaning has various energy sources. The hybrid system consists of a photovoltaic (PV) panel, an electrolyzer, and a proton exchange membrane fuel cell (PEMFC). Additionally, an air source heat pump is used to convert heating and cooling loads to the electric energy. The exergy analysis is applied to main components of the hybrid system. The exergy efficiencies are calculated as the extracted result. Consequently, it was seen that the exergy efficiency of the PV panels remained around 16% when their monthly radiation values are considered. The electrolyzer provided 69% exergy efficiency in the selected time interval. Finally, the exergy efficiency of the PEMFC, the component for which the most detailed exergy analyses were performed, was found to vary between 53% and 55%.
Keywords: PEMFC; PV panel; Exergy efficiency; Hybrid system